Functional analysis of the human somatic angiotensin I-converting enzyme gene promoter. - Testut, P (1993)
Angiotensin I-converting enzyme (ACE) is a key enzyme in the regulation of systemic blood pressure and plays a major role in the renin-angiotensin and bradykinin-kinin systems, at the luminal surface of the vascular endothelia. To identify the promoter region, the transcription regulatory elements and the cell specificity of the ACE gene, five successive DNA deletions of the 5' upstream region (-1214, -754, -472, -343, -132 bp relative to the start site of transcription) were isolated and fused in sense and antisense orientations to the bacterial chloramphenicol acetyltransferase (CAT) reporter gene in the promoterless plasmid pBLCAT3. Promoter activities were measured in transient transfection assays using three different cell lines from rabbit endothelium (RE), human embryocarcinoma (Tera-1) and hepatocarcinoma cells (HepG2). All five fragments of the ACE promoter region directed expression of the CAT gene when transfected into the endothelial and the embryocarcinoma cells, which contain endogenous ACE mRNA and express ACE activity. In contrast only minimal levels of promoter activity were obtained on transfection into hepatocarcinoma cells in which endogenous ACE mRNA and ACE activity were not detected. Transfection of RE and Tera-1 cells demonstrated that promoter activity was defined by the length of the ACE promoter sequence inserted into the construct. The 132 bases located upstream from the transcription start site were sufficient to confer ACE promoter activity, whereas the sequences upstream from -472 bp and between -343 bp and -132 bp were responsible for a decrease of promoter activity. Furthermore, the minimal 132 bp of the ACE promoter contains elements which direct cell-specific CAT expression. In addition, the DNA transfection study in the presence of dexamethasone suggested that the potential glucocorticoid regulatory elements, located in the sequence of the ACE promoter, are not functional.